Chlorinated plastoquinone analogs that inhibit Staphylococcus epidermidis and Candida albicans growth - Kara, Emel Mataracı; Bayrak, Nilüfer; Yıldırım, Hatice; Yıldız, Mahmut; Celik, Berna Ozbek; Tuyun, Amaç Fatih (Folia microbiologica, 2020)
Infectious diseases are the significant global health problem because of drug resistance to most classes of antimicrobials. Interest is growing in the development of new antimicrobials in pharmaceutical discovery. For that reason, the urgency for scientists to find and/or develop new important molecules is needed. Many natural active molecules that exhibit various biological activities have been isolated from the nature. For the present research, a new selected set of aminobenzoquinones, denoted as plastoquinone analogs (PQ1-24), was employed for their in vitro antimicrobial potential in a panel of seven bacterial strains (three Gram-positive and four Gram-negative bacteria) and three fungi. The results revealed PQ analogs with specific activity against bacteria including Staphylococcus epidermidis and pathogenic fungi, including Candida albicans. PQ8 containing methoxy group at the ortho position on the phenylamino moiety exhibited the highest growth inhibition against S. epidermidis with a minimum inhibitory concentration of 9.76 μg/mL. The antifungal profile of all PQ analogs indicated that five analogs (while PQ1, PQ8, PQ9, PQ11, and PQ18 were effective against Candida albicans, PQ1 and PQ18 were effective against Candida tropicalis) have potent antifungal activity. Selected analogs, PQ1 and PQ18, were studied for biofilm evaluation and time-kill kinetic study for better understanding.
Keywords: Staphylococcus epidermidis; Halogenation; plastochinon; vztahy mezi strukturou a aktivitou; Molecular Structure; Candida albicans; Structure-Activity Relationship; Plastoquinone; molekulární struktura; Microbial Sensitivity Tests; biofilmy; antiinfekční látky; mikrobiální testy citlivosti; Anti-Infective Agents; Biofilms; halogenace